Experimental Study of Identifying Emission Sources of Acoustic Signals on the Cylinder Body of a Two-Stroke Marine Diesel Engine - Xuan Thin DONG; Manh Hung NGUYEN (Archives of Acoustics)
In this paper, an experimental method was utilized to investigate acoustic emission (AE) characteristics and to identify emission sources of the nonlinear AE signal on the cylinder body of a large low-speed two-stroke marine diesel engine in real-working conditions on the sea in misfiring and normal firing modes. Measurements focused on the AE signal acquired in a transverse direction in low-frequency (20–80 kHz), medium-frequency (100–400 kHz) and high-frequency (400–900 kHz) ranges. The collected signals were analyzed on the crank angle and crank angle-frequency domains. The results showed that all potential sources of the nonlinear AE signal could be mapped in the low-frequency range. However, only the AE signal caused by the combustion process at around the top dead center could be well-observed in the medium-to-high-frequency range. The findings also revealed that in normal firing conditions, the AE energy radiated by friction in the down-stroke period was smaller than in the up-stroke process due to gas-sealing forces. Moreover, the AE energy in the misfiring condition was higher than in the normal firing state. These outcomes considerably contributed understandings to characteristics of friction and wear around the mid-stroke area of the cylinder on a two-stroke marine diesel engine.